Kapgateophyllum gen. nov. (Acanthaceae) - Deshmukh, Umakant Bhoopati (Phytotaxa, 2021)
Acanthophyllum C.A.Meyer (1831: 210) (Caryophyllaceae Juss.), a genus comprising 80–90 perennial sub-shrubby species with Irano-Turanian distribution pattern extending from Syria to Western China (Bittrich 1993, Ghaffari 2004, Pirani et al. 2014), was first established by Meyer (1831: 210) [type species: Acanthophyllum mucronatum C.A.Meyer (1831: 210)].